Relevancies of Gender Equality in the Novel by Nawal El Saadawi with Literary Works in Indonesia - Fadhillah, Dilla; Hikmat, Ade; Sukardi, Edy (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The topic of gender equality in literary works is still a hot topic of discussion. Starting from awareness of the importance of gender equality in the context of social life, this research aims to examine the issue of gender equality in four novels by Nawal el Saadawi, an Egyptian feminist figure. Qualitative methods were used in this research, with the help of the semiotic approach of Charles Sander Peirce's trichotomy model, to analyze aspects of gender equality contained in literary texts. The research results show that the dominant aspects of gender equality that emerge from these novels are subordination, stereotypes and violence. There is a dominant role of men in the public sphere and in decision-making in a household, cultural stereotypes and societal habits that are biased towards women, and the occurrence of physical, sexual and verbal violence, whether perpetrated by men or fellow women against women. This aspect is relevant to Indonesian literary works with a gender theme published in the period 2017 - 2021. The implications and recommendations of research for contributions to learning activities on the subject of Literary Appreciation in Higher Education are also discussed in this research.